P3.268 A Pilot Study of Genotyping Extrarectal Lymphogranuloma Venereum Strains. (13th July 2013) - Vall-Mayans, M; Isaksson, J; Caballero, E; Barbera, M; Arando, M; Armengol, P; Herrmann, B
Abstract : Background: The first case of LGV in Barcelona was diagnosed in 2005 and since then around 200 cases have been notified up to 2012. All cases have been diagnosed among MSM, 80% of them coinfected with HIV and 97% of the cases had proctitis. Since 2008 some cases have appeared with extrarectal manifestations. Objective: To compare the molecular epidemiology profiles of extrarectal LGV cases diagnosed in Barcelona with profiles reported in rectal cases. Methods: A convenient 14 samples from 9 confirmed LGV cases in 2012 with extrarectal involvement were selected for LGV typing. DNA was extracted from samples using a semi automated system and kept al –80º C. The strains were further analysed by genotyping using a multilocus sequence typing (MLST) based on 5 highly variable gene regions, in addition the ompA gene was sequenced. Results: DNA quality for MLST was suboptimal in some samples. The genotyping pattern showed one single MLST-5 profile (27, 13, 17, 13, 28) among all the samples. In ompA there were two variants (22 and 28), in the 2 cases with ompA variant 22 the samples were obtained from inguinal ganglia. Discussion: The MLST-5 profile in LGV cases from Barcelona is the same as the predominating sequence type found in rectal cases. This is in line with the spread of a single clone, without specific tissue tropism. In ompA the 2 cases with variant 22 were identical to ompA in the reference strain L2/434/Bu, but differed from the currently predominating variant L2b among MSM. Considering the difference in ompA is minor it is more probable that L2b is a classical L2 isolate that has been circulating for a long time but showing now a new spectrum of manifestations. Our study does not support any difference in LGV strains obtained from extrarectal sites or from rectum.